TOOZE, Adam. Crashed: How a decade of financial cri- ses changed the world. New York: Viking, 2018. ISBN: 9780670024933 - Kuttner, Robert (Conjuntura internacional, 2018)
Traduzido do original “The crashed that failed” por Pedro Diniz Rocha.